A COMPARATIVE STUDY ON ARTICLE 241 KOREAN CRIMINAL ACT AND ARTICLE 284 INDONESIAN CRIMINAL CODE. - Ahmad Sobari (Universitas Nasional, 2016)
As the nations that have ratified the Declaration of Human Rights and both have established constitutional rights for citizens in the Constitution of each country, Indonesia and Korea have been conforming the Code /Act to the Convention. This paper is an account of comparing the Law about Act/Code on Adultery, in Korea and in Indonesia. The method is a comparative analysis of the Law, employing normative perspective. The finding of the account is that the Article 241 paragraph (1) and (2) of Law No. 293 of 1963, of Korea (the last amendment on April 5th, 2013 by the Law No. 11731) has in common with the contents of the Article 284 paragraph (1) and (2) of the Indonesian Penal Code or Wetboek van Strafrecht. The Indonesian Penal Code on adultery has been emanated mostly by Pancasila’s ideology in which the principle of Islamic morality and the morality of customary people appear in it; the adultery and fornication are quite contrary to the values of customary law, customs, also quite contrary to the moral values of religions. Keywords: Article 241 Korean Criminal Act, Article 284 Indonesian Criminal Code, Adultery, Sharing The Act/Code. Religious Values, Pancasila